Reduction of WDR81 impairs autophagic clearance of aggregated proteins and cell viability in neurodegenerative phenotypes. - Xuezhao Liu; Limin Yin; Tianyou Li; Lingxi Lin; Jie Zhang; Yang Li (PLoS Genetics)
Neurodegenerative diseases are characterized by neuron loss and accumulation of undegraded protein aggregates. These phenotypes are partially due to defective protein degradation in neuronal cells. Autophagic clearance of aggregated proteins is critical to protein quality control, but the underlying mechanisms are still poorly understood. Here we report the essential role of WDR81 in autophagic clearance of protein aggregates in models of Huntington's disease (HD), Parkinson's disease (PD) and Alzheimer's disease (AD). In hippocampus and cortex of patients with HD, PD and AD, protein level of endogenous WDR81 is decreased but autophagic receptor p62 accumulates significantly. WDR81 facilitates the recruitment of autophagic proteins onto Htt polyQ aggregates and promotes autophagic clearance of Htt polyQ subsequently. The BEACH and MFS domains of WDR81 are sufficient for its recruitment onto Htt polyQ aggregates, and its WD40 repeats are essential for WDR81 interaction with covalent bound ATG5-ATG12. Reduction of WDR81 impairs the viability of mouse primary neurons, while overexpression of WDR81 restores the viability of fibroblasts from HD patients. Notably, in Caenorhabditis elegans, deletion of the WDR81 homolog (SORF-2) causes accumulation of p62 bodies and exacerbates neuron loss induced by overexpressed α-synuclein. As expected, overexpression of SORF-2 or human WDR81 restores neuron viability in worms. These results demonstrate that WDR81 has crucial evolutionarily conserved roles in autophagic clearance of protein aggregates and maintenance of cell viability under pathological conditions, and its reduction provides mechanistic insights into the pathogenesis of HD, PD, AD and brain disorders related to WDR81 mutations.